Predictors of irritability symptoms in mildly depressed perimenopausal women. (April 2021) - de Wit, Anouk E.; Giltay, Erik J.; de Boer, Marrit K.; Nathan, Margo; Wiley, Aleta; Crawford, Sybil; Joffe, Hadine
Abstract: Objective: Irritability is a highly burdensome complaint, commonly, but not universally, linked with depressive symptoms. While increased variability in estradiol has been associated with depressive symptoms during perimenopause, more insight is needed into reproductive hormone dynamics and other factors that predispose perimenopausal women to irritable mood. Methods: Among 50 mildly depressed perimenopausal women (mean (SD) age 48.4 (3.9) years), severity of irritability symptoms (on Symptom Questionnaire Hostility subscale, range 0–23) was assessed weekly for eight weeks, concurrent with potential predictors. Associations between these were examined using generalized estimating equating models. Results: Most women (82.0%) reported having moderate to severe irritability at least once. However, the severity of irritability was highly variable from week-to-week (between-subject mean coefficient of variation [CV] 72.9% and within-subject mean CV 63.7%). In multivariate analyses, less variable serum estradiol levels (standardized β within-person CV −0.23 95%CI [−0.32, −0.14], p < 0.001), greater depression severity (0.45 [0.35, 0.56], p < 0.001), younger age (−0.23, [−0.28, −0.09], p < 0.001), and more frequent vasomotor symptoms (0.14 [0.05, 0.23], p = 0.002) were associated with more irritability. Depression severity explained the largest portion of the variance in irritability, but still not more than 20.3%. Neither crude values, weekly change in, or variability of progesterone or FSH levels were associated with irritability. Conclusions: Irritability was highly prevalent among mildly depressed perimenopausal women. In contrast to depressive symptoms, decreased rather than increased variability in estradiol levels was associated with more irritability. This highlights that irritable mood can be disentangled from depressive symptoms in perimenopausal women and might be linked with different estradiol dynamics. Highlights: Predictors of irritability among mildly depressed perimenopausal women were examined. Irritability was prevalent but very variable in severity from week-to-week. Increased variability in serum estradiol was associated with more irritability. Younger age and more vasomotor symptoms were also associated with more irritability. These associations were independent of depression severity.